Water sorption in pretreated grasses as a predictor of enzymatic hydrolysis yields. (December 2017) - Williams, Daniel L.; Crowe, Jacob D.; Ong, Rebecca G.; Hodge, David B.
Highlights: Diverse conditions for AFEX and AHP pretreatments yield diverse cell wall properties. Water retention value can be employed as a predictor of hydrolysis yields. Compositional changes alone cannot predict yields in AFEX-pretreated biomass. Abstract: This work investigated the impact of two alkaline pretreatments, ammonia fiber expansion (AFEX) and alkaline hydrogen peroxide (AHP) delignification performed over a range of conditions on the properties of corn stover and switchgrass. Changes in feedstock properties resulting from pretreatment were subsequently compared to enzymatic hydrolysis yields to examine the relationship between enzymatic hydrolysis and cell wall properties. The pretreatments function to increase enzymatic hydrolysis yields through different mechanisms; AFEX pretreatment through lignin relocalization and some xylan solubilization and AHP primarily through lignin solubilization. An important outcome of this work demonstrated that while changes in lignin content in AHP-delignified biomass could be clearly correlated to improved response to hydrolysis, compositional changes alone in AFEX-pretreated biomass could not explain differences in hydrolysis yields. We determined the water retention value, which characterizes the association of water with the cell wall of the pretreated biomass, can be used to predict hydrolysis yields for all pretreated biomass within this study.